Survey on hygiene and food safety among kitchen staff in preschools in Podgorica, Montenegro - Milanović Maja; Mugoša Boban; Kolašinac Biljana Popović (Arhiv za Higijenu Rada i Toksikologiju)
Ensuring food safety in kindergartens is crucial for protecting the health of young children. This study assessed the knowledge, attitudes, and practices (KAP) of 113 kitchen employees across the capital of Montenegro, Podgorica. These employees prepare and serve two to four meals daily for children under six. The study aimed to explore correlations between KAP and sociodemographic characteristics and compare self-reported practices with the observed ones. We hypothesized a significant association between the kitchen staff’s knowledge, attitudes, and food handling practices, emphasizing education and training for better hygiene practices. Data were collected using structured questionnaires and checklists. Respondents showed moderate knowledge (77.25±2.69 %) and positive attitudes (95.72±4.53 %), while observed practices were not as high (64.65±27.73 %). A weak positive correlation existed between knowledge and attitudes (r=0.190; p=0.04). Higher education, work experience, and frequent training were associated with better knowledge (p<0.05). Sociodemographic characteristics did not significantly influence attitudes and practices. Multivariate logistic regression indicated knowledge and attitude as predictors, with food safety attitude impacting safe handling practices. Our findings showed moderate knowledge and positive attitudes do not necessarily lead to good practices, as there was no significant correlation between knowledge and self-reported practices or between attitudes and self-reported practices. Education is crucial, as educated staff were more likely to know more about temperature control, cross-contamination prevention, and equipment hygiene. Overcoming external barriers such as infrastructure and time constraints is essential to applying knowledge fostering positive attitudes and improving hygiene practices in kindergartens. This study underscores the need for targeted interventions to ensure safe food handling practices in childcare settings, emphasizing continuous education to maintain food safety standards.